USING AUTHENTIC DOCUMENTARY FILMS TO DEVELOP INTERCULTURAL SENSITIVITY IN SENIOR SECONDARY EFL LEARNERS (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The purpose of this study was to investigate the pedagogical value of authentic documentaries as a scaffolding tool for developing intercultural sensitivity in senior secondary EFL students in Kazakhstan. The study was framed within stage-based models of intercultural competence and task-based media pedagogy, employing a 12-week intervention based on pre-viewing, while-viewing and post-viewing task cycles. One-group pretest-posttest quasi-experimental design with qualitative case study was used with two intact Grade 10-11 classes (N = 32). Quantitative data were collected using a modified and validated Intercultural Sensitivity Scale (ISS) and qualitative data were obtained from weekly reflection journals, video-assisted recall sessions (n = 12), and structured classroom observations. Paired-samples t-tests and reflexive thematic analysis were used in combination to measure progression through the ethnocentric to ethnorelative spectrum. The results indicated statistically significant improvements in overall intercultural sensitivity (t (31) = 8.34, p < .001, d= 1.47) especially in terms of respect for cultural differences and enjoyment of interaction. The qualitative data showed three ways that learning occurred: 1). Narrative transport which filtered out affect, 2). Multimodal awareness which enabled deconstruction of ideologies and 3). Mediated reflection which moved students from Minimization to Adaptation. This research offers a replicable, task-based pedagogical model that combines authentic visual data with critical pedagogy in the development of intercultural competence at the upper-secondary level. Suggestions are offered for curriculum development, instructional materials and media-based assessment, as well as limitations and recommendations for future study.